Thermal stability and thermal oxidation kinetics of PU/CA‐MMT composites. Issue 4 (4th October 2018) - Zhao, Y.; Mo, H.; Jiang, X.; Han, B.; Feng, F.; Wang, D.; Fu, L.; He, L.; Zhang, J.; Shen, J.
ABSTRACT: In this work, we prepared three composites polyurethane (PU)/chlorhexidine acetate (CA), PU/montmorillonite (MMT), and PU/CA‐MMT, and investigated their kinetics of thermal degradation at different heating rates at atmosphere. These materials had good thermal stability and aging resistance. The thermal stability of PU/CA (Tonset: 237.3°C) was not obviously enhanced by the addition of only CA when compared with that of PU (Tonset: 232.3°C), while the thermal stability of PU/MMT (Tonset: 273.4°C) was considerably enhanced by the addition of MMT due to the high thermal stability of MMT. CA‐MMT filler was dispersed and exfoliated in PU more easily than CA or MMT in PU, so the composite PU/CA‐MMT possessed the best thermal stability (Tonset: 285.8°C). In addition, PU/CA‐MMT also had the best resistance to bacterial adhesion and antibacterial ability. The analysis with Flynn‐Wall‐Ozawa method showed that the activation energy of thermal oxidation of PU increased when CA‐MMT was added and thus its anti‐aging ability was enhanced, and the thermal oxidation of these four materials was first‐order reaction. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47002. Abstract :